SELF-EFFICACY, SELF-RATED HEALTH AND PREVALENCE OF PHYSICAL, EMOTIONAL, COGNITIVE AND BEHAVIORAL CHANGES IN TEACHERS - Pereira, Erika Cristina de Carvalho Silva (2024)
The present study aimed to analyze the relationship between self-rated health and the prevalence of physical, cognitive, emotional and behavioral symptoms with levels of self-efficacy in Brazilian teachers during the Covid-19 pandemic. A quantitative, exploratory, descriptive, transversal and inferential survey was carried out. Data analysis was performed using descriptive analysis, Student's t-test, Mann-Whitney test, Spearman correlation, simple and multiple linear regression analysis. 313 Brazilian teachers who were teaching during the Covid-19 pandemic participated in the study. The results showed that self-efficacy averages were statistically lower in teachers with a negative self-assessment of their own health compared to those who self-assessed themselves positively. Simple linear regression analysis pointed to self-rated health as an explanatory variable for self-efficacy (p <0.05). The most frequent emotional, cognitive, physical and behavioral changes were significantly and negatively associated with teachers' self-efficacy beliefs (p <0.05). In the multiple regression model developed, only anxiety significantly explained teachers' self-efficacy. It is concluded that variables such as self-rated health and emotional changes, such as anxiety, explain teachers' self-efficacy levels, and it is therefore essential to develop public policies that promote and develop self-efficacy beliefs, as well as the teacher's overall health.